2015
DOI: 10.18632/oncotarget.5585
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of metabolic pathways by androgen receptor (AR) and its constitutively active splice variant, AR-V7, in prostate cancer cells

Abstract: Metastatic prostate cancer (PCa) is primarily an androgen-dependent disease, which is treated with androgen deprivation therapy (ADT). Tumors usually develop resistance (castration-resistant PCa [CRPC]), but remain androgen receptor (AR) dependent. Numerous mechanisms for AR-dependent resistance have been identified including expression of constitutively active AR splice variants lacking the hormone-binding domain. Recent clinical studies show that expression of the best-characterized AR variant, AR-V7, correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 51 publications
8
74
0
1
Order By: Relevance
“…Interestingly, we found that the promoter of the canonical AR target PSA is co-occupied by AR-V7 and AR-FL whereas the promoter of the UBE2C gene is bound by AR-V7 only (Cao et al 2014), suggesting that the AR-V/AR-FL dimers and the AR-V/AR-V dimers may regulate different sets of target genes. This is supported by transcriptome and metabolome data showing that AR-Vs can regulate some canonical AR targets as well as a distinct set of genes/pathways (Chan, et al 2015; Guo et al 2009; Hu, et al 2012; Li et al 2013; Lu, et al 2014; Shafi, et al 2015). Identifying the respective binding sites for AR-V/AR-FL dimers and AR-V/AR-V dimers across the genome and elucidating whether the genes and pathways regulated by the AR-V/AR-FL dimers fully overlap with those regulated by AR-FL homodimer could be vital in understanding how AR-Vs contribute to castration resistance.…”
Section: Interplays Between Ar-vs and Ar-flmentioning
confidence: 71%
“…Interestingly, we found that the promoter of the canonical AR target PSA is co-occupied by AR-V7 and AR-FL whereas the promoter of the UBE2C gene is bound by AR-V7 only (Cao et al 2014), suggesting that the AR-V/AR-FL dimers and the AR-V/AR-V dimers may regulate different sets of target genes. This is supported by transcriptome and metabolome data showing that AR-Vs can regulate some canonical AR targets as well as a distinct set of genes/pathways (Chan, et al 2015; Guo et al 2009; Hu, et al 2012; Li et al 2013; Lu, et al 2014; Shafi, et al 2015). Identifying the respective binding sites for AR-V/AR-FL dimers and AR-V/AR-V dimers across the genome and elucidating whether the genes and pathways regulated by the AR-V/AR-FL dimers fully overlap with those regulated by AR-FL homodimer could be vital in understanding how AR-Vs contribute to castration resistance.…”
Section: Interplays Between Ar-vs and Ar-flmentioning
confidence: 71%
“…The extent to which AR-Vs regulate unique genes (compared to full length AR) to drive PC progression is under active investigation (27-30). Since AR-V activity is critical for CRPC cell survival and resistance to even the newest generation of AR-targeted therapies, these variants are attractive targets for CRPC treatment (31).…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, the AR consists of four domains: a transactivation domain (encoded by exon 1), a DNA-binding domain (exons 2–3), a hinge region (encoded by the 5′ portion of exon 4), and a ligand-binding domain (exons 4–8), as shown in Figure 1 (2). …”
Section: Androgen Receptor Signalingmentioning
confidence: 99%
“…AR-V7 results from the contiguous splicing of AR exons 1/2/3/CE3, the latter of which is 16 amino acids from exon 3b (see Figure 1) (2, 11, 25). Because this alternative splicing results in the exclusion of the ligand-binding domain, AR-V7 can remain constitutively active in the absence of androgens (25, 27).…”
Section: Biochemical Effects Of Androgen Receptor Variantsmentioning
confidence: 99%
See 1 more Smart Citation